Role Model Bisnis Halal Kopi Lampung dalam Meningkatkan Halal Tourism di Provinsi Lampung (Studi Empiris pada Coffee Shop Dr. Koffie Provinsi Lampung) - Iqbal Iqbal; Muhammad Iqbal Fasa (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The increase in the halal industry has led to halal tourism as a new phenomenon. The purpose of this research is to identify the driving and hindering factors for the halal coffee business and halal tourism in Lampung Province and offer a role model related to its development. This research has an exploratory nature and has adopted a qualitative approach. This study pays special attention to Lampung coffee products. The strong support from Bank Indonesia Lampung Province in increasing the role and support for MSME Coffee is a supporting factor. Meanwhile, obstacles in preparing Lampung Province as a halal tourism destination include awareness and attention of stakeholders to develop halal tourism in this city, which has not yet been developed. The role of the Lampung coffee business model in increasing halal tourism in Lampung Province includes: (1) The Government's Role in Developing GAPOKTAN and Massive Tourism Awareness; (2) One Village One Product; (3) Support for Halal Industry Players; (4) Participation of the Surrounding Community. The government needs to carry out programs on an ongoing basis between agencies. Integration-Interconnection between the Government, Coffee Business Actors, and the Community is a unified whole in order to establish a sustainable business role model.